Faktor-Faktor Yang Mempengaruhi Kinerja Auditor: Independensi, Komitmen Organisasi dan Gaya Kepemimpinan Transformasional - Regita Isna Aisyah; Cris Kuntadi; Ujang Hanief Mustofa (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of Independence, Organizational Commitment and Transformational Leadership Style on Auditor Performance. This article reviews the factors that influence Auditor Performance, namely Independence, Organizational Commitment and Transformational Leadership Style, a study of tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Independence influences auditor performance; 2) Organizational Commitment influences Auditor Performance; and 3) Transformational Leadership Style influences Auditor Performance.